Evidencing student success and career outcomes among business and creative industries graduates. Issue 5 (3rd September 2019) - Jackson, Denise; Bridgstock, Ruth
ABSTRACT: The teaching performance of higher education institutions is increasingly gauged by graduate employment outcomes. Measuring outcomes in full-time employment terms does not capture the complexities of underemployment, the rise of portfolio careers, the constraints of the labour market and graduate motivations for working arrangements that can allow greater flexibility and work-life balance. This study explores the career outcomes of Business and Creative Industries graduates using both traditional measures (full-time employment outcomes) and a suite of broader measures that examine career satisfaction, perceived employability, perceived career success, underemployment, and graduate motivations for seeking new roles. Findings confirm disciplinary differences in graduate experience, and raise some broad concerns about the quality of graduate employment, particularly given the lack of improvement in outcomes over time since course completion. Findings suggest graduates are optimistic about their career futures, despite unmet expectations â€" particularly on income.